THE ROLE OF MUSIC CULTURE LESSONS IN THE GROWTH OF THE CONSCIOUSNESS OF THE STUDENT YOUTH AND NATIONAL THINKING - Usmanov Azizbek Azamatovich; Nurullayev Farrukh Gaibulloyevich (Western European Studies, 2023)
The article includes music classes, extracurricular and extracurricular activities such as clubs, holidays, entertainment nights in order to further develop the process of cultivating consciousness and National thinking in students in different ways. This serves as an important tool for the effective implementation of the education of students in every possible way.
Keywords: innovative technology; music; value; spiritual